Pré-tratamento de efluente de curtume por bactérias e enzima lipolíticas - Lima, Vivian de Oliveira (2015)
Industrial wastewaters present different physiochemical characteristics, requiring specific studies for choose the correct treatment for each effluent, ensuring more efficiency, taking into account environmental requirements. Many kinds of industries, including tannery, potentially produce effluents with high content of oil and grease (O&G). Those compounds can cause operational problems and interfere on the performance of biological treatment systems. For these reasons, in general, is recommended the preliminary removal of O&G. The enzymatic hydrolysis of lipids has proven promising in pretreatment of wastewaters like an alternative for physiochemical methods. The aim of this study was isolate microorganisms from tannery effluent able to produce extracellular lipase, apply them in the pretreatment in laboratorial scale of this effluent and compare their effects with the commercial product Enzilimp® and with PPL enzyme (porcine pancreas lipase Sigma Aldrich®). Were isolate 14 strains from tannery's effluent. The strain MOV7 (positive staphylococci), that presented the greatest enzymatic index, was used on the tests. Were done three preliminary tests with the objective to evaluate the time and the influence from inoculum concentration, from effluent dilution and aeration. After, were made the DCCR to evaluating the influence from temperature, inoculum and effluent concentration, and pH on the variables responses CODt, CODs, O&G e Acid Index during 48 hours in fermentation system and 24 hours after in aerobic system. In the end of the tests were concluded that the tannery effluent is a potential source of lipolytic bacteria and those strains have similar behavior to Enzilimp®. During 72 hours (48 hours in fermentative conditions and 24 in aerated conditions) the pretreatment reached the reduction of 75% of O&G and 47% of CODt with MOV7 and 52% of O&G and 30% with PPL enzyme. The PPL enzyme caused the increasing of 1,1g CODt on each gram from added enzyme. When in natura, the increasing of inoculum concentration gave no better results on treatment. However, the effluent dilution promoted the decreasing of parameters COD, O&G and AI for the different inoculums. The aeration was effective on reduction from organic matter in dilutions between 12,5 and 62,5 mL.L-1. Was observed that the temperature and pH influenced significatively the system's work with better results on 30°C and 8,0, respectively.